The development of a threshold curve for the understanding of concussion in sport. (July 2017) - Hoshizaki, T Blaine; Post, Andrew; Kendall, Marshall; Cournoyer, Janie; Rousseau, Philippe; Gilchrist, Michael D; Brien, Susan; Cusimano, Michael; Marshall, Shawn
Much of what is known concerning human brain injury thresholds is based upon impacts to cadavers and animal models that were used to generate the Wayne State Concussion Tolerance Curve (WSTC) and similar curves. These curves are the foundation for predictive metrics used in standard development as well as helmet design. These curves were based upon a very narrow range of impacts; impacts whose characteristics differ greatly from how the head is impacted in sport. This research examines the uses of time-based curves like the WSTC in the context of understanding mechanisms of brain injury and head protection. Published linear/rotational acceleration magnitude/duration data from Hybrid III laboratory reconstructions of brain injury events were plotted. This research further develops the understanding of injury thresholds in comparison to threshold curves such as the WSTC and Brain Injury Curve Leuven. The data demonstrate the relationships between magnitude and duration of dynamic response on minor traumatic brain injury (mTBI) in sport.